Rebuilding Stouffer Place - Wilkinson, Jordan C. (Kansas State University, 2011)
College and university campuses have the potential to organize buildings, outdoor spaces, pedestrian corridors, roadways, parking lots, and infrastructure all within one cohesive and unified place. Dynamic but unified spaces are typically the result of thoughtful architecture, landscape architecture, and years of planning. Recognizable design styles, material use, and plant palettes work together to create something bigger than simply a collection of buildings, transportation corridors, and outdoor spaces. Each building, group of buildings, series of spaces, transportation feature, and infrastructural component needs to be designed and implemented with the entire campus in mind to be truly successful. When planned correctly, a unified campus can harbor innovation, provide inspiration, and initiate interaction. Stouffer Place Apartments has evolved into a secluded housing development within the midst of the busy University of Kansas (KU) campus. Apartments are only available to graduate students, international students, students with families, non-traditional students, and post-doctoral researchers. Stouffer Place has maintained a quiet and peaceful atmosphere at the corner of 19th and Iowa in Lawrence, Kansas since 1957. Like so many of the university housing developments built after World War II, Stouffer Place is full of aging infrastructure, providing the basis for a discussion of a new or renovated development on the site (Casey-Powell 1999, 86). Not only are the aging Stouffer Place buildings an eyesore to many people in the community, but their existing arrangement limits community interaction and shared space. Additionally, many of the Stouffer Place apartment buildings are near the end of their lifetime, but they can they be recycled, reused, and deconstructed to create dynamic spaces for the residents. In short, Stouffer Place can be redeveloped to create a new model of affordable, sustainable, and self-sufficient on-campus apartments that attract and retain students as well as create a higher quality of life. With the growing trend of sustainable building practices, KU’s Department of Student Housing (DSH) has an immense opportunity to transform this student community into a model for other universities nationwide. By implementing a design strategy that successfully reuses and phases out the existing built infrastructure of the site, a place that facilitates sustainable living and community interaction will be created. Through this project, the culture and identity of Stouffer Place is revealed and catalyzed, using the missions of KU and DSH to create a plan that supports, sustains, and creates.
Keywords: Stouffer Place; University of Kansas; Student housing; Sustainable redevelopment; Landscape Architecture (0390)